Halotriazolium Axle Functionalised [2]Rotaxanes for Anion Recognition: Investigating the Effects of Halogen‐Bond Donor and Preorganisation. Issue 37 (11th August 2014) - Mercurio, James M.; Knighton, Richard C.; Cookson, James; Beer, Paul D.
Abstract The anion‐templated synthesis of three novel halogen‐bonding 5‐halo‐1, 2, 3‐triazolium axle containing [2]rotaxanes is described, and the effects of altering the nature of the halogen‐bond donor atom together with the degree of inter‐component preorganisation on the anion‐recognition properties of the interlocked host investigated. The ability of the bromotriazolium motif to direct the halide‐anion‐templated assembly of interpenetrated [2]pseudorotaxanes was studied initially; bromide was found to be the most effective template. As a consequence, bromide anion templation was used to synthesise the first bromotriazolium axle containing [2]rotaxane, the anion‐binding properties of which, determined by 1H NMR spectroscopic titration experiments, revealed enhanced bromide and iodide recognition relative to a hydrogen‐bonding protic triazolium rotaxane analogue. Two halogen‐bonding [2]rotaxanes with bromo‐ and iodotriazolium motifs integrated into shortened axles designed to increase inter‐component preorganisation were also synthesised. Anion 1H NMR spectroscopic titration experiments demonstrated that these rotaxanes were able to bind halide anions even more strongly, with the iodotriazolium axle integrated rotaxane capable of recognising halides in aqueous solvent media. Importantly, these observations suggest that a halogen‐bonding interlocked host binding domain, in combination with increased inter‐component preorganisation, are requisite design features for a potent anion receptor.